Some New Data on Muslim Literature in Oriental Languages - Nametak, Fehim (Prilozi za orijentalnu filologiju, 2017)
The present paper deals with data concerning some poets from Bosnia and Herzegovina so far unknown, who wrote their poetry in Turkish and Persian. They are: Nabi Tuzlak (Nabi Tuzlawi), whose autograph is kept at Ghazi Husrev-bey Library (No. 40p7), and who lived in the first half of the XVIIth century; Abdi Tuzlak (Abdi Tuzlawi) (GHB, No. 4007); and Savabi Tuzlak (Sawabi Tuzlawi) (GHB No. 4007), a poem by each of them is to be found in the same codex, that of Edai Sinan Celepi(Adai Sinan Celebi), of Sarajevo, whose poem Mi'ragiyya is in the same copy. The poet Senai Mostarac (Tanad al-lVIostaril also had his own collection of poem (GHB, No. 2290), unknown until now. The works of the poets: Mustafa-bey Atlagić Safi (GHB, temporary inventory, No. 1457) and Mehmed Meyli (GHB No. 2012) and Mehmed Cohadžić Djudi (GHB, No. 1452) are also registered here for the first time.